Example of fractional equations, Mathematics

Example of Fractional Equations:

Example:

Solve the fractional equation (3x +8)/x +5 =0

Solution:

Multiply both sides of the equation by the LCD (x).

(x) ((3x +8)/x +5) = (0) (x)

3x + 8 + 5x = 0

8x + 8  = 0

Now solve the equation such as an ordinary linear equation.

Step 1. Transpose the +8 from the left-hand to the right- hand side of the equation by changing its sign.

8x = 0 - 8

8x = -8

Step 2. Using Axiom 4, divide both sides of the equation by 8.

8x/8 = -8/8

x = -1

Step 3. Check the root.

(3(-1)+8)/-1 +5 = (-3+8)/-1 +5 = -5 + 5 =0

The root checks.

Posted Date: 2/9/2013 2:42:31 AM | Location : United States







Related Discussions:- Example of fractional equations, Assignment Help, Ask Question on Example of fractional equations, Get Answer, Expert's Help, Example of fractional equations Discussions

Write discussion on Example of fractional equations
Your posts are moderated
Related Questions
Example   Given the graph of f(x), illustrated below, find out if f(x) is continuous at x = -2 , x = 0 , and x = 3 . Solution To give answer of the question for each

64% of the students within the school play are boys. If there are 75 students in the play, how many are boys? To ?nd out 64% of 75, multiply 75 by the decimal equivalent of 64%

Determine or find out the area of the inner loop of r = 2 + 4 cosθ. Solution We can graphed this function back while we first started looking at polar coordinates.  For thi

Audrey is creating a increased flowerbed which is 4.5 ft by 4.5 ft. She requires computing how much lumber to buy. If she requires knowing the distance around the flowerbed, which


1+3+5+7+9+11+13+15+17+19

Derivatives of Inverse Trig Functions : Now, we will look at the derivatives of the inverse trig functions. To derive the derivatives of inverse trig functions we'll required t


If a, b and c are in harmonic progression with b as their harmonic mean then, b  = This is obtained as follows. Since a, b and c are in

Properties of Cross product If u, v and w are vectors and c is a number then u → * v → = -v → * w →                                                       (cu → ) * v → =